Bus manufacturing workshop scheduling method with routing buffer. (7th May 2020) - Han, Zhonghua; Zhang, Jingyuan; Wang, Shiyao; Qi, Yuanwei
Aiming at solving the problem that the moving route is complicated and the scheduling is difficult in the routing buffer of the bus in the manufacturing workshop, a routing buffer mathematical programming model for bus manufacturing workshop is proposed. We design a moving approach for minimising the total setup cost for moving in routing buffer. The framework and the solution of the optimisation problem of such a bus manufacturing workshop scheduling with routing buffer are presented. The evaluation results show that, compared with the irregularly guided moving method, the proposed method can provide a better guide line for the bus movement in the routing buffer by reducing the total setup time of all buses processed at the next stage, and a better scheduling optimisation solution with minimise maximum total completion time.